A METHOD FOR CALCULATING THE INFORMATION SECURITY RISK (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2022)
The article discusses the issues of identifying threats and vulnerabilities of information security violations. To protect information, it is necessary to create computer attack detection systems. Explanations were given on the concept of cyber attacks and their types were affected. No organization is currently sufficiently protected from cyber attacks. All organizations should develop a special plan to combat cybercriminals. A special plan allows you to prepare for emergencies, resist emerging threats and quickly restore the effect of the attack. The need to know the threatening factors and understand their tactics, methods and procedures to protect against cyber attacks is emphasized. The process of information protection should be comprehensive and continuous, carried out at all stages of the creation and use of automated data processing tools. The main methods of information protection are given.
Keywords: Information security, cyber attacks, cybercrime, information protection, threats, vulnerability.